Between “High” Literature and Middle-literature: Poetics of the short story “Ballet Libretto” by M. Kuzmin - Полякова, Євгенія Олегівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article focuses on the poetics of the short story “Ballet Libretto” (1917) by M. Kuzmin. Researchers practically do not study the poetics of  his short stories “from modern life” (preferring stylized prose), which is due to the generally accepted opinion of them as second-rate literature. Nevertheless, such a characterization of these works does not seem to be entirely correct with a deeper analysis of  M. Kuzmin’s unstylized short stories, in which the peculiarities of poetics are found that are inherent in more artistic, at first glance, short stories. Thus, in the “Ballet Libretto” the extensive intertext, the abundance of references to various cultural phenomena and works of art are of particular interest. The text contains mentions the names and works of famous French writers (“The Rules of the Thirteen” by O. Balzac, articles and libretto by T. Gauthier, “The Devil in Love” by J. Cazot). At the same time, the novel also encrypts subtle, but important references to famous works of art (“Shagreen leather” and “Gobshek” by O. Balzak, “Crime and Punishment” by F. Dostoevsky), personalities (J.-B. Lully, Moliere) and cultural phenomena (Russian ballet, musical theater, French national opera). Irony, as a permanent feature of the poetics of  M. Kuzmin’s works is also manifested in the short story “Ballet Libretto”, which is facilitated by playing on characters’ names, subtle allusions to the symbolism philosophy and replicas of the heroes themselves. Despite the fact that the short story can be interpreted as a story with a fascinating plot, the work has another, “hidden” plan, manifested in the references and allusions, which indicates an elegant author’s game with the reader, which does not allow to characterize the work as template. Identified poetics’ features (the presence of irony, rich intertext, many references to the phenomena of world culture and art) are also characteristic of some other short stories “from modern life” by M. Kuzmin (“Platonic Charlotte”, “The Same Eyes”, “A Kindred Visit” etc.) To what extent these features are characteristic of other similar M. Kuzmin’s works, which have not been the subject of analysis by literary critics yet, is an actual question for further research.